PSIII-32 Nutrient and amino acids digestibility of animal protein byproduct in swine, determined using an in vitro model. (7th December 2018) - Tiwari, U; Kerr, B; Jha, R
Abstract: Animal protein byproducts (APB) are produced in slaughter houses and rendering plants derived from a wide array of inedible carcass tissues including blood, feathers, bones, and other miscellaneous tissues. Along with their high mineral content, APB are also high in energy and amino acids (AA). The objective of this study was to characterize the variation in nutrient composition of APB, determine apparent ileal digestibility (AID) of energy and AA, and derive a prediction equation for ileal energy digestibility. A total of 13 APB were collected from different sources in US and grouped into 5 general categories: feather meal (FM), meat meal (MM), meat and bone meal (MBM), blood meal (BM), and poultry byproduct meal (PBM). Their nutrient profiles were determined using standard analysis methods, with the AID of nutrients and AA determined using an in vitro swine assay. Stepwise regression was used to determine effect of nutrient composition on AID of energy. Gross energy (GE) and crude protein (CP) in APB ranged from 4, 100 to 5, 797 kcal/kg and 53 to 97%, respectively. The AID of GE of MBM2 and PBM1 was higher ( P ˂ 0.05) than MM1 and MM2. The AID of CP of BM was higher ( P < 0.05) than MBM. The AID of lysine (Lys) in BM1 and BM2 was higher ( P < 0.05) than MBM2 and FM2. The AID of Tryptophan in BM1 and BM2 was higher ( P < 0.05) than PBM1 and MBM2. Overall, MBM provided the highest amount of digestible GE whereas AID of most essential AA was higher in BM than other APB. These data support the use of APB in swine diets to provide a highly digestible source of most AA. However, except for BM, the remaining APB provided insufficient Lys required for optimum growth of swine.